The role of pregnane X receptor (PXR) in substance metabolism - Lv, Ye; Luo, Yi-Yang; Ren, Hui-Wen; Li, Cheng-Jie; Xiang, Zhi-Xin; Luan, Zhi-Lin (Frontiers in Endocrinology, 2022)
As a member of the nuclear receptor (NR) superfamily, pregnane X receptor (PXR; NR1I2) is a ligand-activated transcription factor that plays a crucial role in the metabolism of xenobiotics and endobiotics in mammals. The tissue distribution of PXR is parallel to its function with high expression in the liver and small intestine and moderate expression in the kidney, stomach, skin, and blood-brain barrier, which are organs and tissues in frequent contact with xenobiotics. PXR was first recognized as an exogenous substance receptor regulating metabolizing enzymes and transporters and functioning in detoxification and drug metabolism in the liver. However, further research revealed that PXR acts as an equally important endogenous substance receptor in the metabolism and homeostasis of endogenous substances. In this review, we summarized the functions of PXR in metabolism of different substances such as glucose, lipid, bile acid, vitamin, minerals, and endocrines, and also included insights of the application of PXR ligands (drugs) in specific diseases.